Back-yard medfly is a key factor in area-wide management in Southern Europe. Data from Attiki Greece, 38 - Economopoulos, A. P.; Rempoulakis, P. (ENTOMOLOGIA HELLENICA, 2018)
A twelve month Mediterranean fruit-fly, medfly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) record was kept in a small back-yard with 8 medfly host fruit trees in a neighborhood about 7 km from the center of Athens, from November 2015 till November 2016. Similar small back-yards exist in the whole area. Large commercial host tree plantations exist at about 80 km west of Athens, while backyards with fruit trees exist in villages or small towns in-between. McPhail yellow bottom traps (one per tree) with Biolure (3 separate dispensers of ammonium acetate, trimethylamine, and putrescine) and a water solution of 1.5% sodium tetraborate and a few drops of kitchen detergent were used. Traps were examined approximately every week and water solution renewed. The Biolure dispensers were renewed every 3-4 months. On the average (medflies per tree-trap per day) 1.4 flies were trapped in November, less than 1 were trapped between December and early May, except mid-April when 1.7 flies were trapped. From June till October high records were detected. In June-July records up to over 52.7 flies were observed (highest population peak in the year), while in September October records up to 34.3 flies were observed (second highest population peak in the year). The sex ratio of trapped flies was almost always in favor of females, usually between 60-100%. An increase of medfly catches was always detected following Biolure dispensers renewal. In case Area-wide SIT applications are considered, the reproductive behavior of released flies in these special environments must be well investigated.